INVERSE PROBLEM OF STURM-LIOUVILLE OPERATOR WITH NON-SEPARATED BOUNDARY VALUE CONDITIONS AND SYMMETRIC POTENTIAL - A.Sh. Shaldanbayev; A.A. Shaldanbayeva; A.Zh. Beisebayeva; B.A. Shaldanbay (Academic Scientific Journal of Computer Science, 2019)
In this paper, we prove uniqueness theorem, by one spectrum, for a Sturm-Liouville operator with non-separated boundary value conditions and a real continuous and symmetric potential. The research method differs from all previously known methods and is based on internal symmetry of the operator generated by invariant subspaces.